Adverse events in the placebo arm of maintenance therapy trials in advanced ovarian cancer: A systematic review and meta-analysis. (July 2022) - Simon, Sandy; Francis, Katherine E.; Dalrymple, Janene E.; Gebski, Val; Lord, Sarah J.; Friedlander, Michael; Lee, Chee Khoon
Abstract: Background: Maintenance treatment is standard of care for front-line (FL) and platinum-sensitive recurrent ovarian cancer (PSROC) following response to chemotherapy. Adverse events (AEs) on maintenance therapies are common and usually attributable to investigational treatments but could also be unrelated. Randomised controlled trial (RCT) with blinded placebo design is the gold standard for determining the relative differences in efficacy and AEs between treatment arms. We performed a meta-analysis to quantify AE rates in placebo arms of RCTs to determine AEs not due to investigational agents. Methods: We performed an electronic search to identify eligible RCTs in FL and PSROC settings. Data from placebo arms were extracted and pooled using the inverse variance method to determine the risk of any AE, overall and specific grade 3 or higher (G ≥ 3) AEs, and AE-related treatment delay, reduction and discontinuation. Results: We identified 13 eligible RCTs (FL, N = 8; PSROC, N = 5) with 2224 patients who received placebo (FL, N = 1541; PSROC, N = 683). The majority experienced an AE of any grade (FL, 93.0%; PSROC, 95.2%). Substantial proportions experienced G ≥ 3 AEs (FL, 14.6%; PSROC, 18.2%). In the FL setting, AEs led to treatment delay in 14.4%, dose reduction in 4.1% and discontinuation in 2.6%. Findings were similar for PSROC: 8.4%, 5.5% and 2.1%, respectively. Conclusions: AEs not due to investigational agents are common in ovarian cancer patients in maintenance therapy RCTs. Potential explanations include the nocebo effect, residual toxicities from previous treatment or underlying disease. Further research is required to identify better approaches to assessing AEs in this population. Highlights: The majority of patients on maintenance placebo experienced adverse events (AEs). AEs were associated with dose delays, reductions and discontinuation of placebo. The underlying aetiology is complex and likely involves the nocebo phenomenon. AEs in randomised trials may not reflect true investigational treatment toxicities.